2022
DOI: 10.3389/fcvm.2022.1047700
|View full text |Cite
|
Sign up to set email alerts
|

Role and molecular mechanism of traditional Chinese medicine in preventing cardiotoxicity associated with chemoradiotherapy

Abstract: Cardiotoxicity is a serious complication of cancer therapy. It is the second leading cause of morbidity and mortality in cancer survivors and is associated with a variety of factors, including oxidative stress, inflammation, apoptosis, autophagy, endoplasmic reticulum stress, and abnormal myocardial energy metabolism. A number of studies have shown that traditional Chinese medicine (TCM) can mitigate chemoradiotherapy-associated cardiotoxicity via these pathways. Therefore, this study reviews the effects and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 174 publications
0
2
0
Order By: Relevance
“…Ginsenosides are the most crucial active substances in ginseng, which have antioxidant, apoptosis inhibiting, autophagy regulating, and other cardiotoxicity-reducing effects ( Hou et al, 2022 ; Lv et al, 2022 ). It has been found that Dox can cause apoptosis and autophagy in H9c2 cardiomyocytes, and ginsenoside Rb1 can attenuate Dox-induced myocardial injury by a mechanism that may be realized by inhibiting Dox-induced autophagy ( Li et al, 2017 ; Zhang et al, 2017 ; Zhu et al, 2017 ).…”
Section: Effects Of Chinese Herbal Medicine and Its Constituent Compo...mentioning
confidence: 99%
“…Ginsenosides are the most crucial active substances in ginseng, which have antioxidant, apoptosis inhibiting, autophagy regulating, and other cardiotoxicity-reducing effects ( Hou et al, 2022 ; Lv et al, 2022 ). It has been found that Dox can cause apoptosis and autophagy in H9c2 cardiomyocytes, and ginsenoside Rb1 can attenuate Dox-induced myocardial injury by a mechanism that may be realized by inhibiting Dox-induced autophagy ( Li et al, 2017 ; Zhang et al, 2017 ; Zhu et al, 2017 ).…”
Section: Effects Of Chinese Herbal Medicine and Its Constituent Compo...mentioning
confidence: 99%
“…Salvia miltiorrhiza and Ligusticum Chuanxiong are commonly employed to improve blood circulation and eliminate blood stasis, while sophora flavescens is often used to alleviate internal heat. 54 …”
Section: The Comprehension and Management Of Cardiotoxicity Induced B...mentioning
confidence: 99%
“…Salvia miltiorrhiza and Ligusticum Chuanxiong are commonly employed to improve blood circulation and eliminate blood stasis, while sophora flavescens is often used to alleviate internal heat. 54 The management of cardiotoxicity involves addressing the development of TCM compound preparation, which is primarily characterized by a deficiency in Qi and Yin. The medications used in this treatment approach primarily aim to replenish Qi and Yin.…”
Section: Dovepressmentioning
confidence: 99%